2015
DOI: 10.1186/s12933-015-0219-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycated albumin and the risk of micro- and macrovascular complications in subjects with Type 1 Diabetes

Abstract: BackgroundWe investigated the relationship between the glycemic indices glycated albumin (GA) and glycated hemoglobin (HbA1c) and the progression of diabetic vascular complications [diabetic nephropathy (DN) and carotid artery atherosclerosis (CAA)] in subjects with type 1 diabetes (T1D).MethodsA total of 154 participants with a median follow-up of 2.8 years were enrolled in this retrospective longitudinal study. We recruited T1D subjects who had regularly measured urine albumin-creatinine ratios and estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…This is supported by another experiment conducted in Korean patients with type 1 diabetes mellitus. Glycated albumin levels, rather than HbA 1c , were associated with DN . In our experiment, we included Chinese patients with T2DM and confirmed that GA had a stronger indicative power than HbA 1c , and that HbA 1c was not associated with presence of DN in T2DM.…”
Section: Discussionsupporting
confidence: 58%
“…This is supported by another experiment conducted in Korean patients with type 1 diabetes mellitus. Glycated albumin levels, rather than HbA 1c , were associated with DN . In our experiment, we included Chinese patients with T2DM and confirmed that GA had a stronger indicative power than HbA 1c , and that HbA 1c was not associated with presence of DN in T2DM.…”
Section: Discussionsupporting
confidence: 58%
“…Nayak et al [10] reported that there was biological variability in the glycation gap despite its long-term consistency in an individual, and this biological variability would be measurable under conditions of relatively stable glycaemic control. Recent reports proposed the use of glycated albumin [11,12] and glycated albumin/HbA 1c ratio as indices of chronic diabetic complications independently of HbA 1c [13,14]. We observed that the individual mean value of the glycated albumin/HbA 1c ratio over time showed long-term consistency and a highly significant inverse correlation with the glycation gap when using simultaneous measurement of HbA 1c and glycated albumin instead of fructosamine [15].…”
Section: Introductionmentioning
confidence: 69%
“…In another smaller study with 154 type 1 DM patients followed over 2.8 years, the progression to nephropathy was associated only with GA and not with A1C. The authors did not find association between these two glycemic markers and the cardiovascular outcomes (58).…”
Section: Ga As a Predictor Of Long Term Complication In Dmmentioning
confidence: 86%
“…However, there is still controversy if mean glycemia itself or glycemic variability is the main determining factor for chronic damage in DM (16). Recent studies have evaluated the predictive potential value of tests that are more associated with the short term glycemia and that can be used as alternative markers for A1C, such as GA (8,16,17,58).…”
Section: Ga As a Predictor Of Long Term Complication In Dmmentioning
confidence: 99%